PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN DIGITAL UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI KALIKALONG - Muhammad Ferdian Syaifullah; Tanti Trinawati; Ratri Nur Fauziah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
Learning problems at Kalikalong State Elementary School show that students are still less focused on learning because the material delivered is still lectures and students cannot think abstractly, so the solution to this problem is by developing learning media. The purpose of this study is 1) to find out the development of learning media; 2) to find out the feasibility of developing learning media that includes validity, practicality, and effectiveness. The method in this study is the R&D method with the ADDIE model. The media developed is a digital game media from the Canva platform. The game developed contains the Science material